The interferon signaling antagonist function of yellow fever virus NS5 protein is activated by Type I interferon - Laurent-Rolle, Maudry (2014)
To successfully establish infection Flaviviruses have to overcome the antiviral state induced by type I interferon (IFN-I). The nonstructural NS5 proteins of several flaviviruses antagonize IFN-I signaling. Here we show that yellow fever virus (YFV) inhibits IFN-I signaling through a unique mechanism that involves binding of YFV NS5 to the IFN-activated transcription factor STAT2 only in cells that have been stimulated with IFN-I. This NS5-STAT2 interaction requires IFN-I-induced tyrosine phosphorylation of STAT1 and the K63-linked polyubiquitination at a lysine in the N-terminal region of YFV NS5. We identified TRIM23 as the E3 ligase that interacts with and polyubiquitinates YFV NS5 to promote its binding to STAT2 and trigger IFN-I signaling inhibition. Our results demonstrate the importance of YFV NS5 in overcoming the antiviral action of IFN-I and offer a unique example of a viral protein that is activated by the same host pathway that it inhibits.